Equipment Maintenance Using IR Thermography - Sithiravelautham, Dinesh; Sabaliauskas, Artūras; Čikotienė, Dalia (Jaunųjų mokslininkų darbai, 2018)
This work attempts to show some case studies through Infrared thermography involvements in the industrial maintenance. Initially critical points of the essential or very important machines and electrical circulation units for the production have to investigated. The points where we observed abnormal temperature variations were further analysed using other advanced tools like: vibration analyzer, Laser alignment tool, Oil analyser and Ultrasonic detector. The main objective is to prove that by implementing a good scheduled thermography survey one can decrease major expenses and save time. In addition, it has the capacity to contribute to the reliability of maintenance and minimize unexpected plant shutdowns dramatically in small and large-scale industries.
Keywords: Infrared (IR) Thermography; reliability, emissivity; conductivity; reflection; ambient temperature